Physical, magnetic, morphological, and optical properties of isotropic magnetorheological elastomers with cobalt as fillers for assistive sensor devices applications - Nasruldin, Akmal Arif; Shabdin, Muhammad Kashfi; Awang Kechik, Mohd Mustafa; Kien, Chen Soo; Pah, Lim Kean; Shaari, Abdul Halim; Abdul Karim, Muhammad Khalis; Nazmi, Nurhazimah (Springer, 2024)
Cobalt particles are often used as fillers in magnetorheological elastomer (MRE) due to their potential advantages. This study aimed to assess the physical, morphological, magnetic, and optical properties of cobalt-based MRE (Co-MRE). To achieve this, several isotropic samples with different concentrations of cobalt and polydimethylsiloxane (PDMS) were created. Finite Element Method Magnetics (FEMM) 2D simulation software and a Vibrating Sample Magnetometer (VSM) were used to assess the magnetic properties. Morphological properties were observed with a Field Emission Scanning Electron Microscope (FESEM) and physical properties were examined using X-Ray Diffraction (XRD). Ultraviolet–Visible (UV–Vis) and Photoluminescence (PL) spectroscopy were used to study the optical properties. FEMM 2D showed that 7 wt% of Co-MRE had the highest magnetic flux density. VSM indicated that 7 wt% of Co-MRE had the strongest magnetic saturation. Morphological properties revealed that 7 wt% of Co-MRE had a rougher surface than 0–5 wt%. XRD showed that 7 wt% of Co-MRE had more cobalt elements. UV–Vis indicated that 5 wt% of Co-MRE had a precise result with some noise. PL spectroscopy showed that 7 wt% of Co-MRE had a higher emission peak and a broader shape at 475–525 nm excitation wavelength, while 0 wt% had a broader shape graph at 550–600 nm. While these properties are beneficial, it is important to balance the sensitivity and elasticity of MRE for stable applications in assistive sensor devices. © The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature 2024.